A economia popular solidária frente às transformações contemporâneas no mundo do trabalho - Buzzatti, Alan Patrik (2007)
The present work treats the recent process of transformations, many of them still in course, in the capitalist's way of production and of the formation of the popular solidary economy in Brazil starting from the years of 80 s. The importance of approaching these themes in part starting from the critical reality of exploration and hesitation of the life conditions of the working class as well as, the search for solutions on the part of these workers before such reality. The changes implemented in the development of the capitalism starting from the years of 70 s, are fundamentally characterized for the productive and organizational restructuring of the capitalism through the substitution of Taylorism/Fordism for Toyotism, introduction and renewal of the machinery, through to growing robotization and informatization of the work processes and hegemony of neoliberal politics. In this negative context to the work, different alternatives of work generation and income have been theorized and practiced by a number more and more significant of workers. If in a first moment, they are demonstrated as alternatives of little collective synergy amid precariousness and fragmentation of the informal work, in a second moment, in the most recent period, starting from the end of the years of 1990, it is being an important road in the construction of collective alternatives and no production capitalists and distribution of the accomplished work. In Brazil, the Solidary economy along the last ten years was constituted, besides a work alternative and production under new bases (self-management, cooperation, solidarity, democracy, participation) in a political praxis that involves thousands of militant, so much those originating from traditional fronts of the workers' fight as the syndical movement, student, feminist, anti-racist, environmentalist as well as new linked militants by the construction of convergence spaces as the editions of the World Social Forum. The development and future sustainability of this movement of solidary economy are still difficult to project for the adverse context in that are inserted, however they are real bases in the accumulation of forces of the working class not only in Brazil but in matter in Latin America where grows contemptible the workers' fights for another project of society different from the capitalist hegemonic